Dietary fishmeal levels affect the volatile compounds in cooked muscle of farmed large yellow croaker Larimichthys crocea. (21st June 2017) - Mu, Hua; Wei, Zehong; Yi, Lina; Liang, Haiou; Zhao, Limei; Zhang, Wenbing; Mai, Kangsen
Abstract: A comparative study on the volatile compounds in cooked muscle of wild and farmed large yellow croaker (LYC) was conducted. The two farmed LYC groups were fed with diets containing 44% (CF) and 25% (LF) of fish meal (FM) respectively. Results showed that 48 volatiles, including aldehydes, alcohols, ketones, hydrocarbons, aromatics, acids, esters, furans and miscellaneous compound, were detected in cooked fillets. The LF group had significantly lower amounts of total aldehydes and ketones, higher content of miscellaneous compound in cooked fillets than that in the CF and wild groups ( p < .05). Compared with the wild group, the LF group had significantly lower amounts of total alcohols, acids and esters, while the CF group had significantly lower amounts of total aldehydes, higher content of total ketones in cooked muscle ( p < .05). According to the principal component analysis (PCA), some volatiles (propanal, nonanal, etc.) could be considered as sensitive indicators to classify cooked muscle samples. In conclusion, differences in the volatiles in the cooked muscle between the wild and farmed LYC have been found. Low level of dietary FM (25%) changed the volatile profiles in cooked fillets of farmed LYC. A PCA may be useful to screen potential volatiles to classify cooked muscle samples in this study.